Iron Deficiency Anaemia is Associated with Decreased Levels of Macrophage Migration Inhibitory Factor and Monocyte Chemoattractant Protein-1. Issue 3 (July 2015) - Oran, Mustafa; Tulubas, Feti; Mete, Rafet; Aydin, Murat; Yildiz, Z.Deniz; Yilmaz, Ahsen; Gurel, Ahmet
No abstract available